2013
DOI: 10.1111/joor.12099
|View full text |Cite
|
Sign up to set email alerts
|

Association between underweight and taste sensitivity in middle‐ to old‐aged nursing home residents in Sri Lanka: a cross‐sectional study

Abstract: Low taste sensitivity may be one factor related to undernutrition, which is a major problem in developing countries. The purpose of this cross-sectional study was to examine the association between underweight, one indicator of undernutrition, and taste sensitivity in middle- to old-aged Sri Lankan nursing home residents. Participants were 946 residents with BMI of <25·0 from 25 nursing homes. Data were obtained on height, weight, taste sensitivity, subjective taste ability, sex, age, ethnicity, number of year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
5
3
Order By: Relevance
“…Previous work also suggested that an underweight status was associated with impaired bitter identification in middle‐ to old‐aged nursing home residents (Fuchida et al, 2013), which are in contrast to the present result that the underweight group exhibited a higher proportion of impaired salty identification. On the one hand, the present subjects came from a Smell and Taste clinic, and their age ranged from 18 to 95, which is different from the previous study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous work also suggested that an underweight status was associated with impaired bitter identification in middle‐ to old‐aged nursing home residents (Fuchida et al, 2013), which are in contrast to the present result that the underweight group exhibited a higher proportion of impaired salty identification. On the one hand, the present subjects came from a Smell and Taste clinic, and their age ranged from 18 to 95, which is different from the previous study.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work also suggested that an underweight status was associated with impaired bitter identification in middle-to old-aged nursing home residents (Fuchida et al, 2013), which are in contrast to the present result that the underweight group exhibited a higher…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Research has suggested that taste perception is impaired during normal aging (Bartoshuk 1989; Boesveldt et al 2011; Cowart 1989; Heft and Robinson 2010; Methven et al 2012; Mojet et al 2001; Murphy 1993; Schiffman 1997; Stevens 1996), even more so in hospitalized older adults (Solemdal et al 2014; Toffanello et al 2013). Taste loss may be one of several factors contributing to poor appetite, reduced dietary intake, and weight loss in elderly patients (Chen et al 2001; Fuchida et al 2013; Schiffman and Graham 2000; Schiffman and Wedral 1996; Ship et al 1996). Lastly, patients whose primary complaint is taste loss have also shown nutritional abnormalities (Malaty and Malaty 2013; Mattes and Cowart 1994; Mattes-Kulig and Henkin 1985).…”
Section: Taste Food Intake/preference and Metabolic Diseasementioning
confidence: 99%